False alarms and the positive predictive value of smartphone-based hyperacuity home monitoring for the progression of macular disease: a prospective cohort study - Faes, Livia (Eye (Lond), 2021)
BACKGROUND: Home monitoring of hyperacuity allows early detection of progression in exudative neovascular age-related macular degeneration (nvAMD) and diabetic macular oedema (DMO). However, false alarms may pose a significant burden to both patients and healthcare professionals alike. PURPOSE: To assess the false alarm rate and positive predictive value of smartphone-based home monitoring of nvAMD and DMO. METHODS: Patients treated with anti-angiogenic therapy in a pro re nata scheme for nvAMD or DMO at the Medical Retina service (Lucerne, Switzerland) between March and June 2016 were included in this prospective cohort study. The home monitoring test Alleye (Oculocare Ltd, Switzerland) provided a session score from 0–100 in addition to a traffic-light system feedback via the smartphone application. Three consecutive “red” scores were considered as a positive test or alarm signal. Specificity, 1-specificity (false alarm rate) and the predictive value for optical coherence tomography-based disease progression were analysed. RESULTS: 73 eyes of 56 patients performed 2258 tests in 222 “follow-up periods”. Progression was observed in 141 periods (63.5%). The specificity of the test was 93.8% (95% CI: 86.2–98.0%), the false alarm rate 6.1% (95% CI: 2.0–13.8%), and the positive predictive value 80.0% (95% CI: 59.3–93.2%) for the detection of progression. CONCLUSION: False alarm rates for the detection of progression in macular disease via home monitoring is low. These findings suggest that home monitoring may be a useful adjunct for remote management of nvAMD and DMO.